2021
DOI: 10.3389/fmars.2021.702101
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Carbohydrate and Protein Levels Affect the Growth Performance of Juvenile Peanut Worm (Sipunculus nudus): An LC–MS-Based Metabolomics Study

Abstract: The peanut worm (Sipunculus nudus) is an economically important fishery resource in China. To determine how dietary carbohydrate and protein levels affect the growth performance of juvenile S. nudus and identify the mechanisms underlying observed patterns, five isoenergetic and isolipidic diets with different levels of carbohydrate and protein were formulated and fed to juvenile S. nudus; the experimental groups were referred to as EG1, EG2, EG3, EG4, and EG5, respectively. After 90 days of feeding, S. nudus h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Diverse phenotype traits of animals are reported that they are regulated by transcripts and metabolites and metabolome sequencing analyses could obtain different or additional information for phenotypic diversity (Yang et al, 2018;Huang et al, 2021). Integrated transcriptome and metabolome analyses have been utilized in numerous species such as Coilia nasus (Xu et al, 2016), Pinctada fucata martensii (Zhang et al, 2021), and Eriocheir sinensis (Wang et al, 2021) to analyze for phenotypic differences.…”
Section: Introductionmentioning
confidence: 99%
“…Diverse phenotype traits of animals are reported that they are regulated by transcripts and metabolites and metabolome sequencing analyses could obtain different or additional information for phenotypic diversity (Yang et al, 2018;Huang et al, 2021). Integrated transcriptome and metabolome analyses have been utilized in numerous species such as Coilia nasus (Xu et al, 2016), Pinctada fucata martensii (Zhang et al, 2021), and Eriocheir sinensis (Wang et al, 2021) to analyze for phenotypic differences.…”
Section: Introductionmentioning
confidence: 99%
“…ARG regulates L-arginine to produce ornithine and urea. Ornithine is a precursor of polyamines, a vital substance for regulating cell growth and promoting cell proliferation ( 41 ). As an intermediate of the urea cycle, L-arginine can alleviate ammonia poisoning with the urea cycle and avoid metabolic disorders caused by excess ammonia ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an intermediate of the urea cycle, L-arginine can alleviate ammonia poisoning with the urea cycle and avoid metabolic disorders caused by excess ammonia ( 42 ). Additionally, L-arginine can be used for ribosomal synthetic proteins ( 41 , 43 ). On the other hand, studies have found that dietary protein content significantly affects amino acid metabolism ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, bacterial community functions related to metabolism were dominant in different surrounding environment (48.68%-50.47%) and mainly included amino acid metabolism, carbohydrate metabolism, and energy metabolism. This result may be related to the need of S. nudus to exhibit a high anabolic capacity to obtain sufficient energy for maintaining normal development of the organism (Yang et al, 2020;Huang et al, 2021).…”
Section: Relationships Between Bacterial Communities In Different Sur...mentioning
confidence: 99%